Pengembangan E-MODUL Fisika Dasar untuk Pembelajaran Online Berbasis Android Mobile - Rindi Wulandari (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2020)
WHO (The World Health Organization) has declared Covid-19 a pandemic that has posed a contemporary threat to humans. This pandemic has succeeded in making mass decommissioning of activities, including activities in the field of education, this has led to a massive transition in the world of higher education to promote online education. Module is one of the teaching materials that can be used in learning and can support the effectiveness of the learning process. The purpose of this research is to create basic physics e-modules in order to access learning materials easily, efficiently, and fun based on android. This stage of research is preliminary study, desaign development, and testing. The results of this study in the form of e-modules and feasibility test surveys on a limited scale, e-modules that have been made show a fairly good feasibility results.